Potential forest plantation species: Leucaena leucocephala / Wan Mohd Nazri Wan Abd Rahman …[et al.] - Wan Abd Rahman, Wan Mohd Nazri; Kasim, Jamaludin; Mohd Sahal, Mohd Saiful Akbar; Khalid, Fairuz (2009)
Fast growing and high yielding tree plantations are becoming an important source of wood in tropical countries. The future supply of wood will be met from these planted forests as opposed to managed natural forests. In Malaysia, Leucaena leucocephala is widely regarded as a shade tree because of its fast growth (lead tree) compared to other commercial tropical trees. The Malaysian Agricultural Research Development Institute (MARDI) has used this species for shade and wind protection for a variety of crops, especially during early growth and for animals feed. The objectives of the paper were to compare the stem yield of leucaena leucocephala with rubber wood and acacia mangium. This study revealed that stem yield of leucaena leucocephala ranged from 30.83 to 134.23 tons ha-1 for the tree age of 3 years-old to 16 years-old. Based on data comparison with Acacia and rubber wood, leucaena leucocephala was found to be a suitable alternative for forest plantation species with a better stem yield recovery.